2002
DOI: 10.1182/blood-2001-12-0339
|View full text |Cite
|
Sign up to set email alerts
|

Sustained integrin ligation involves extracellular free sulfhydryls and enzymatically catalyzed disulfide exchange

Abstract: Studies have suggested a pivotal role for free sulfhydryls in platelet integrin function, and enzyme-mediated reduction of disulfide bonds on platelets has been implicated. The platelet fibrinogen receptor ␣ IIb ␤ 3 is the best-studied platelet integrin and serves as a model system for studying the structure-function relation in this family of adhesion receptors. The demonstration of free sulfhydryls on the exofacial domain of purified ␣ IIb ␤ 3 , specifically in its activated conformation, prompted us to expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
215
0
6

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(235 citation statements)
references
References 42 publications
14
215
0
6
Order By: Relevance
“…These data also confirm our previous observation that FXIII can bind directly to platelets [23]. However, in another study, we showed that PDI-dependent platelet adhesion is specific to platelet integrin-mediated adhesion [12,13]. Thus, the addition of FXIII following established platelet integrin-fibrinogen interaction, as in the present work, leaves FXIIIA PDI activity free to enhance this interaction.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These data also confirm our previous observation that FXIII can bind directly to platelets [23]. However, in another study, we showed that PDI-dependent platelet adhesion is specific to platelet integrin-mediated adhesion [12,13]. Thus, the addition of FXIII following established platelet integrin-fibrinogen interaction, as in the present work, leaves FXIIIA PDI activity free to enhance this interaction.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, on the basis of our earlier findings that PDI plays a mediatory role in platelet adhesion [11][12][13] and that FXIIIA exerts PDI activity [10], we sought to examine the relative contributions of FXIII PDI or transglutaminase activity to platelet adhesion to fibrinogen.…”
Section: Thrombosis Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Free thiols become available on the platelet surface upon activation [10] and those present on integrin α IIb β 3 provide a direct target for redox modification [33]. Thiol-disulphide exchange within α IIb β 3 , catalysed by an endogenous isomerase activity [34], by PDI [11,35], or by ERP5 [36] is necessary for transition to its active conformation. Thus the thiol redox state of α IIb β 3 influences platelet adhesive function and any agent that modifies this redox state may interfere with platelet aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…Another model suggests that integrin conformation is regulated by reduction of the disulfide bonds and possibly involves protein-disulfide isomerase (PDI) (17)(18)(19). PDI regulates disulfide exchange and conformationally induced shedding of Lselectin (20).…”
mentioning
confidence: 99%